Experimental Study of the Reduction in Ceramide Content in Fingernails Due to Nail Polish Remover Use - Kazuhisa Maeda; Nao Iwashita (Cosmetics, 2022)
The amount and distribution of ceramide, an intercellular lipid, in the fingernails of three Japanese women in their twenties were examined by high-performance liquid chromatography and antibody staining. In addition, the structural changes of fingernail cross sections were examined after fingernails were immersed in an acetone-based nail polish remover solution. The acetone-treated fingernails had a lower water content and higher water evaporation than the inner forearm skin and healthy fingernails, suggesting that they had compromised moisturizing and barrier functions and were more susceptible to roughness and damage. These results also suggest that, compared to healthy fingernails, rough fingernails are more prone to breakage and damage. Furthermore, it was found that the amount of ceramide decreased when fingernails were immersed in nail polish remover solution. The distribution showed ceramide to be present in the ventral and dorsal regions of the free edge of the fingernail plate. After immersion in nail polish remover, the three-layered structure of the free edge of the plate was intact, but the dorsal distal edge of the plate peeled off. Gaps were observed inside the free edge of the plate, which should have been layered. These results show that the frequent use of nail polish remover may worsen condition of fingernails.